Analisa Pengaruh Variasi Bentuk Buritan Kapal Terhadap Hambatan Total Pada Kapal Twin Screw Propeller Menggunakan Metode CFD - Zulqurna'in Rizal; Santoso Mardi; Julianto Eko (Politeknik Perkapalan Negeri Surabaya, 2018)
One aspect that needs to be reviewed in improving the performance of the ship is the optimal bow and stern form so that the total resistance of the ship can be minimized. In the field oc Naval Architecture, it is necessary to start the innovation to test the hull forms, especially stern. which has the smallest resistance. In this study we discuss the testing of the stern model on the 5000 GT Ferry ship with a variety of stern shapes and speeds using the CFD method. The aims to get the stern shape with the smallest total resistance value. Stern 3D modeling and calculation of ship resistance using the Maxsurf software. Analysis conducted using the Computational Fluid Dynamic (CFD) method approach, it can provide an overview of fluid distribution that occurs with predetermined conditions and variations. From the CFD simulation results, at a speed of 15, 17, and 21 knot obtained a sternshaped ship that has the smallest total resistance value, that is (without sternbulb and hanger), 143,633 kN at a speed of 15 knot, 281,333 kN at a speed of 17 knot and 433,333 kN at 21 knot. While at the speed of 19 knot the model that has the smallest total resistance value is model 3 (with hanger), with a value of 374,467 kN.